Decadal Shifts in Wind Patterns Reduced Continental Outflow and Suppressed Ozone Trend in the 2010s in the Lower Troposphere Over Japan. Issue 22 (20th November 2018) - Okamoto, S.; Tanimoto, H.; Hirota, N.; Ikeda, K.; Akimoto, H.
Abstract: The large increase in the springtime free tropospheric ozone over the western and eastern North Pacific over the last decades has been linked to the increase in anthropogenic emissions in China. However, the increasing trend at Mt. Happo, Japan, has been unexpectedly suppressed since 2008, by 5–10 ppbv. In this paper, we analyzed the tropospheric ozone records at Mt. Happo, along with the changes in climate and anthropogenic emissions. We revealed, based only on observational data, that the changes in climate pattern play an important role in controlling the decadal ozone trend. We found that the persistent La Niña‐like wind pattern during 2008–2013 reduced the export of polluted air masses from East Asia to the western Pacific, even though Chinese emissions continued to increase. On the other hand, an El Niño‐like wind pattern during 1992–1996 and enhanced storm track activity during 2000–2006 enhanced the export of polluted air masses from East Asia, contributing to the accelerated ozone trends. The climate modulations were identified in the O3 trends at the surface sites in western and central Japan and at a remote marine boundary layer site, Minamitorishima. Without this climatic effect driven by the persistent La Niña‐like wind pattern, the ozone trend would have been further upward over the North Pacific in the late 2000s to the early 2010s. Key Points: Tropospheric ozone level at Mt. Happo, Japan, dropped in the late 2000s, despite increasing Chinese emissions Persistent La Niña‐like wind pattern has reduced long‐range transport from East Asia via weakened westerly winds Without the persistent La Niña‐like wind pattern, the ozone trend over Japan would have been further upward in the late 2000s